PKM KELOMPOK KREATIF TUKANG BANGUNAN DESA SUKOGIDRI DENGAN KETERAMPILAN MEMBUAT TULANGAN BETON DARI BAMBU - Muhtar Muhtar; Amri Gunasti; Abadi Sanosra (Jurnal Abdi Insani, 2022)
Sukogidri Village is an underdeveloped village towards an independent village. The topography of the village is in the form of highlands and hills where many bamboo plants grow which is great potential to be utilized. However, bamboo has not been used strategically and has not been of high selling value. One of the benefits of bamboo is used as concrete reinforcement. The basic problem is that the village community, especially the craftsmen, do not yet know about bamboo as concrete reinforcement, so they need mentors and motivators to increase community empowerment. The objectives of this activity include the achievement of the level of empowerment of members of the creative community group and the growth of the entrepreneurial spirit of the craftsmen through counseling and training. Methods for implementing the activities include: (1) providing guidance and training on how to produce concrete reinforcement from bamboo for the structure of simple houses; (2) providing training on bamboo treatment as concrete reinforcement; (3) providing counseling about the marketing and economic prospects of bamboo. The results achieved are the level of empowerment of members of the Community Creative Group increases. From the results of practical and theoretical tests, 80% of the builders did not make mistakes, and only 19.70% made mistakes. As many as 19.70% of the builders are skilled workers but still, need further assistance. And 80.30% of the builders are skilled workers who are independent and do not need further assistance. It can be concluded that training and guidance on bamboo as concrete reinforcement can improve the entrepreneurial spirit of the community with the formation of the Community Creative Group.